PROSES STOKASTIK KELAHIRAN-KEMATIAN DENGAN DUA JENIS KELAMIN SECARA KELOMPOK PADA PROSES YULE-FURRY - samsuryadi, samsuryadi (MATEMATIKA, 2001)
The research is carried out to build stochastic model from cluster birth-death process with two sexes on Yule-Furry process, since the formula or stochastic model from that stochastic process is not presented yet, where as a lot of phenomena are represented about that stochastic process. Model development is basically to find postulate form and differential equation. The final results of this research are postulate and differential equation from stochastic process, partial differential equation for transition probability generating function, and joint moment generating function.